2021
DOI: 10.1080/21655979.2021.1995101
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TRPM2-AS regulates microRNA miR-138-5p and PLAU (Plasminogen Activator, Urokinase) to promote the progression of gastric adenocarcinoma

Abstract: Gastric adenocarcinoma (GAC) is a common malignant tumor, accounting for 95% of gastric cancers. However, the effects and regulatory mechanisms of long non-coding RNA TRPM2-AS (TRPM2-AS) in GAC have not been fully explored. Our study investigates the action mechanism of TRPM2-AS in GAC. After performing quantitative Real-Time polymerase chain reaction or western blotting, we found that the levels of TRPM2-AS and Plasminogen Activator, Urokinase (PLAU) were upregulated in GAC, whereas the level of miR-138-5p wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…We found that lncRNA TRPM2-AS might target a total of 410 miRNAs predicted by public databases. Among these miRNAs with high scores, five miRNAs, including miR-1291, miR-6852-5p, miR-138-5p, miR-218-5p, and miR-93-3p, were previously shown to participate in cancer pathogenesis [ 26 , 45–48 ]. This study validated that only miR-1291, miR-6852-5p, and miR-138-5p were increased by lncTRPM2-AS knockdown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that lncRNA TRPM2-AS might target a total of 410 miRNAs predicted by public databases. Among these miRNAs with high scores, five miRNAs, including miR-1291, miR-6852-5p, miR-138-5p, miR-218-5p, and miR-93-3p, were previously shown to participate in cancer pathogenesis [ 26 , 45–48 ]. This study validated that only miR-1291, miR-6852-5p, and miR-138-5p were increased by lncTRPM2-AS knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…This study validated that only miR-1291, miR-6852-5p, and miR-138-5p were increased by lncTRPM2-AS knockdown. Among these three miRNAs, only miR-138-5p has published evidence that it was directly targeted by lncRNA TRPM2-AS and thus regulating downstream signaling, e.g., PI3K/AKT in non-small cell lung cancer, syndecan 3 (SDC3) in ovarian cancer, and urokinase in gastric adenocarcinoma [ 20 , 21 , 26 ]. MicroRNA-138 expression was associated with chemosensitivity and radiosensitivity of EC treatment [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, PLAU is an important modulator of tumorigenesis and progression. PLAU is overexpressed in several tumors, including head and neck squamous cell carcinoma (HNSCC) (7), gastric adenocarcinoma (8) and breast cancers (9). PLAU participates in tumor progression by promoting tumor cell proliferation, cell migration, invasion, and epithelial-mesenchymal transition (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%